OCEANS 2015 - Genova 2015
DOI: 10.1109/oceans-genova.2015.7271638
|View full text |Cite
|
Sign up to set email alerts
|

High Duty Cycle (HDC) sonar processing interval and bandwidth effects for the TREX'13 dataset

Abstract: Unlike conventional Pulsed Active Sonar (PAS), which listens for target echoes in between short-burst transmissions, High Duty Cycle (HDC) sonar attempts to detect echoes amidst the continual interference from source(s) transmitting with nearly 100% duty cycle. HDC sonar presents an additional processing parameter, not available with PAS, which is the processing interval. The processing interval is a selectable subset of time within a CAS repetition cycle used for coherent processing. Hence, the choice of proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Once the effect of spreading is resolvable by the signal resolution, losses will occur, and as a result, further increases in time or bandwidth will not deliver the predicted gains. Previous work has shown that the background suppression follows theoretical predictions [2]. Here, we focus on the environmental effects on signal losses.…”
Section: Performance Vs Processing Time/bandwidthmentioning
confidence: 80%
See 2 more Smart Citations
“…Once the effect of spreading is resolvable by the signal resolution, losses will occur, and as a result, further increases in time or bandwidth will not deliver the predicted gains. Previous work has shown that the background suppression follows theoretical predictions [2]. Here, we focus on the environmental effects on signal losses.…”
Section: Performance Vs Processing Time/bandwidthmentioning
confidence: 80%
“…III. THE LCAS'15 SEATRIAL DATA Previous experimentation [2] has shown that one can estimate the coherence limit of the acoustic channel using the CTLFM signal. However, using a single, sub-banded CTLFM waveform, there is no way to determine if the channel's coherence limit is due to time spreading only or due to Doppler spreading only ('singly spread' channel), or spreading in both time and Doppler ('doubly spread' channel).…”
Section: Performance Vs Processing Time/bandwidthmentioning
confidence: 99%
See 1 more Smart Citation
“…One may want to maintain the same bandwidth for a CAS system as for the PAS system it might replace. This will provide a significant increase in the time-bandwidth product but may not produce the increase in gain anticipated if there are significant coherence limitations associated with the acoustic channel [188][189][190][191]. If sub-band processing is applied, it can not only provide a higher measurement rate [147,192] but can significantly mitigate the effects of limited time coherence of the channel [191] in CAS mode.…”
Section: Cas Versus Pas Modesmentioning
confidence: 99%
“…To experimentally examine the advantages and limitations of CAS (or HDCAS) with respect to the more traditional PAS mode [193], a series of sea trials have been conducted. Among others, the 2013 sea campaign Target and Reverberation Experiment (TREX‐2013) conducted in the Atlantic was partly devoted to evaluate the impact of pulse duration on echo statistics [194] and evaluate sonar performance with respect to environmental spreading effects, the target's physical extent and Doppler effects [190, 195]; the Littoral Continuous Active Sonar (LCAS) joint research and multinational project started in 2015 and, led by NATO STO CMRE, aims at the evaluation of CAS performance in littoral waters, generally characterised as a high‐reverberation environment, hence more challenging for CAS. Two sea campaigns were conducted in 2015 and 2016, respectively, in Mediterranean coastal waters in the context of LCAS project [191].…”
Section: Acoustic Signal Processingmentioning
confidence: 99%